(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Quarantine and lockdown, combined with restriction to the movement of people, along with measures like universal use of masks, social distancing, tracking, testing, isolation and specialized centers to manage COVID-19 patients, have been successful in the control and spread of the virus in China and most Asian countries, unlike in Europe and America. This review is written to provide information on quarantine, isolation and lockdown in the context of COVID-19 management. The quarantine and lockdown from historical, socio-cultural, and its effect on special circumstances, for example, the internal and international migrants, daily wage workers, refugees, and the ways in which countries have managed this issue, including the measures taken by Nepal to manage the quarantine and lockdown is briefly presented in this review.